2021
DOI: 10.30744/brjac.2179-3425.ar-61-2021
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for Preconcentration and Determination of Silver in Aqueous Samples using Cloud Point Extraction

Abstract: For the selective extraction of silver, a cloud point extraction (CPE) procedure was developed. After synthesizing the solvation species through the reaction of silver ions with 2, 4-dimethyl pentane-3-one (2,4 DMP), the salting-out agent (0.4 mol L-1 NaNO3) was added at 35 °C and, after 10 min, Triton X-114 was used to separate silver ions from aqueous solution. The type and quantity of salting-out agent, silver ion, temperature, heating time, and surfactant volume were all examined as important factors deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…T=60 °C was reported to be the optimum temperature for maximum extraction efficiency for both ions examined, according to the findings. When it comes to CPL production and extraction, this temperature achieves the strongest thermodynamic equilibrium [43]. After measuring the extraction content K ex at each temperature, Figure 8 was created by plotting the logarithm value K ex versus 1/T K. As shown in Table 3, which was utilized to calculate the thermodynamic date for each metal ion [42].…”
Section: Surfactant Volume Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…T=60 °C was reported to be the optimum temperature for maximum extraction efficiency for both ions examined, according to the findings. When it comes to CPL production and extraction, this temperature achieves the strongest thermodynamic equilibrium [43]. After measuring the extraction content K ex at each temperature, Figure 8 was created by plotting the logarithm value K ex versus 1/T K. As shown in Table 3, which was utilized to calculate the thermodynamic date for each metal ion [42].…”
Section: Surfactant Volume Effectmentioning
confidence: 99%
“…After constructing a calibration curve of the metals, Zn (II) and Cd (II) metal ions were determined extensively under optimal conditions [43]. Table 3 also lists the analytical parameters that were measured.…”
Section: Food Samples Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of approaches have been performed to detect AA levels, including spectrofluorimetry, UV spectroscopy, and electrophoresis. However, these need to be more practical and require re-evaluation owing to inadequate accuracy and precision . The application of the colorimetric method reported by a study showed a better accuracy, where the results were in close agreement with a confidence level of 95% against the iodometric technique. , Several studies have reported that the most preferred technique for determining AA levels in fruits and vegetables is a spectrophotometry approach using Fourier transform infrared (FTIR) spectroscopy owing to the rapidity, selectivity, sensitivity, reliability, and consistency …”
Section: Introductionmentioning
confidence: 99%
“…Cloud point extraction (CPE) is a modified LLE approach that uses micelles as an extraction solvent instead of hazardous organic solvents [10][11][12][13]. Among the preconcentration procedures, CPE represents a simple and environmentally friendly procedure for separation of inorganic and organic species in different samples [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%